HUBUNGAN MOTIVASI BELAJAR DENGAN SELF DIRECTED LEARNING READINESS (SDLR) MAHASISWA TINGKAT III AKADEMI KEBIDANAN ANUGERAH BINTAN TANJUNG PINANG TAHUN 2017 - Marzanita, Fitria; Utami, Risqi (Universitas Batam, 2017)
It is to be underline that learning motivation of students cites to one of the extrinsic elements of Self-Directed Learning Readiness (SDLR). In fact, Anugerah Bintan Midwifery Academy is one of the Higher Education institutions which initiates competency based learning education system in from of Problem Based Learning for their students. Therefore, the researchers want to identify the correlation between the learning motivation of students and self-directed learning readiness as well as its impacts on students learning outcomes. To deal with this issue, the analytical survey by using cross-sectional approach was employed. As the population, it was the third-year students of 57 respondents in total which were selected through total sampling teachnique. This study lasted six months from february to august 2017. The data instrument used to collect the and simple linier regression. The finding shows that there is a correlations between the learning motivation and SDLR presented by (Ï-value =0,009). There is a positive influence the learning motivation and SDLR presented by (tcal = 2.702) withÂ 12% of total influence, therefore the regression formula is Y = 74.011 + 1.015X. This regression formula means that whenever there is 1 augmentation on learning motivation, it affects 1.015 augmentation on SDLR. This correlation claims a positive relation that the higher the learning motivation, the higher the SDLR would be. Based in this finding, the researchers come to the conclusion that there is a positive correlation on learning motivation and self-directed learning readiness of third-year students of Anugerah Bintan Midwifery Academy to be precise. Finally, for future researches on the same topic to put more focus on the factors affected the state of self-directed learning readiness of students.Â